Learning strategies for gifted students in primary schools: A systematic review - Meidias Abror Wicaksono; Yuli Kurniawati Sugiyo Pranoto; Diana, Diana (Jurnal Pendidikan Anak, 2025)
This study aims to identify, map, and analyze various learning strategies for gifted and talented students in primary schools based on recent scientific literature. The method used is a Systematic Literature Review (SLR) conducted following the PRISMA 2020 framework. The sample comprised 28 scientific articles published between 2020 and 2024, retrieved from SCOPUS, Web of Science, ProQuest, Garuda, and SINTA databases. Data were collected using an extraction sheet containing variables such as title, author, year, country, method, sample, and findings related to learning strategies for gifted students. The data were analyzed descriptively and thematically to identify patterns, trends, implementation constraints, and implications associated with various learning strategies. The results reveal that differentiated instruction, digital technology integration, and project based constructivist approaches can optimize the development of gifted students, although their implementation in primary schools is still limited due to insufficient teacher training, technological constraints, and the absence of adequate implementation guidelines. The novelty of this study lies in its comprehensive synthesis that explicitly compares previous reviews and highlights the unique contribution of this work in linking instructional strategies with policy implications and teacher professional development. Furthermore, this study provides practical implications for teachers, curriculum developers, and policymakers by offering evidence based recommendations to enhance instructional practices. In conclusion, an adaptive learning approach based on the needs of gifted students requires teacher training, curriculum adjustment, and strengthened technological infrastructure to ensure effective and sustainable learning practices.